Analisis Kadar Flavonoid Ekstrak Etanol Cabe Rawit, Cabe Keriting, Dan Cabe Besar Menggunakan Metode Spektrofotometri UV-VIS - Fadillah, Nur; Baits, Muzakkir; Maryam, St (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Chili fruit is a type of medicinal plant which is used as an anti-inflammatory, analgesic, antiflatulant, headache and rheumatism because it contains capsaicin, capsantin, carotenoids, essential alkaloids, resin, volatile oil, multivitamins. This study aims to determine the total flavonoid content of three types of chili using the UV-VIS spectrophotometry method. This type of research is laboratory experimental using a spectrophotometer method based on the determination of extract levels and quarcetin standards. The stages of this study began with sample preparation, extraction of compounds in the sample using ethanol solvent, and ended with the determination of total flavonoid content of the chili fruit sample and quarcetin standard. This study found that the average total flavonoid content for samples of bird's eye chilies, large chilies, and curly chilies was 19.695; 31.72; and 16.011 mg QE/g extract. The percentage of total flavonoid content in bird's eye chilies, large chilies, and curly chilies in this study were 1.9695%; 3.172%; and 1.6011%.